1994
DOI: 10.1111/j.1346-8138.1994.tb03273.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Human Papillomavirus Type 60 in Plantar Cysts and Verruca Plantaris by the In situ Hybridization Method Using Digoxigenin Labeled Probes

Abstract: At first, punctate keratotic lesions are induced by HPV 60. HPV 60 induces irregular elongation of the rete ridges into the dermis. Plantar cysts probably form as a result of the traumatic implantation of HPV 60 infected epidermis with irregularly long and narrow rete ridges into the dermis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 7 publications
(10 reference statements)
0
36
1
Order By: Relevance
“…8 Alternatively, in the nontumorigenic lesions, these antigens include the viral antigens such as human papillomavirus antigens (VV), bacterial superantigens (LP), HLA antigens, cutaneous lymphocyte-associated antigen (PV). 9,10 Moreover, the damaged keratinocytes might produce more cytokines that recruit more immunocytes. 11 The gradual increase in B cell count from non-tumorigenic, to pre-tumorigenic, and finally to tumorigenic lesions go in line with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…8 Alternatively, in the nontumorigenic lesions, these antigens include the viral antigens such as human papillomavirus antigens (VV), bacterial superantigens (LP), HLA antigens, cutaneous lymphocyte-associated antigen (PV). 9,10 Moreover, the damaged keratinocytes might produce more cytokines that recruit more immunocytes. 11 The gradual increase in B cell count from non-tumorigenic, to pre-tumorigenic, and finally to tumorigenic lesions go in line with other groups.…”
Section: Discussionmentioning
confidence: 99%
“…The case described here is interesting because the wart had features of both pigmented and ridged warts, suggesting that ridged warts can be pigmented. A case of HPV-60-induced wart reported by Kawase et al [10]also seems to retain a ridged pattern on the smooth surface of a flat pigmented lesion. In our case, it was demonstrated that increased melanin granules in both keratinocytes and melanin blockade melanocytes were the primary contributors to clinical pigmentation.…”
Section: Discussionmentioning
confidence: 99%
“…Vacuolated cells were also seen in the granular cell layers. To determine the causative HPV type, in situ hybridization was applied to formalin-fixed, paraffin-embedded sections using digoxigenin-labelled HPV-1, -2, -4, -60, -63 and -65 DNA probes, as described elsewhere [10]. Positive signals in the nuclei of the keratinocytes distributed mainly in the upper part of the epidermis were only seen when HPV-60 DNA was used as a probe (fig.…”
Section: Case Reportmentioning
confidence: 99%
“…Histopathologically, lesions demonstrate stereotypical enlarged keratinocytes in upper epidermis with gray-blue cytoplasm, enlarged round nuclei with pale chromatin, and one or multiple nucleoli (Figure 3).The Immunohistochemistry findings showed the HPV antigens [26].In electron microscopy, The nuclei are clarified with maeginated chromatin, and crystalline viral particles are present in nucleoplasm and in the prominent nucleoli ( Figure 6). Under an electron microscope, HPV5 virions purified from pooled scales of EV patients and virus-like particles (VLP) assembled from a purified recombinant baculoviruses expressing the L1 major capsid protein of HPV5 were observed( Figure 7) [27].…”
Section: Clinical and Histologic Findingsmentioning
confidence: 98%